أثر الرضا عن الحياة على أداء معلمي المدارس الثانوية في اليمن: The Impact of: Life Satisfaction on the Performance of Secondary School Teachers in Yemen - Al-gailani, Amin Abdellah; Al-hidabi, Dawood Abdulmalak (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث للتعليم دور ريادي ذو تأثير كبير وملاحظ في تطوير المجتمع؛ ويُمثل المعلمون فيها عَصبَ العملية التعليمية وأساسها؛ وذلك يدعو إلى الاهتمام بهم؛ وتذليل العقبات التي تواجههم ليؤدوا دورهم التربوي، ومن هذا المنطلق، هدفت الدراسة الحالية إلى اختبار مدى تأثير الرضا عن الحياة الاقتصادية، الرضا عن الحياة الصحية، التقدير الاجتماعي، على الأداء الوظيفي لدى معلمي المدارس الثانوية في اليمن. وقد استخدم الباحثان المنهج الوصفي المسحي الذي يعدُّ ملائمًا لطبيعة هذه الدراسة وأهدافها، كما اعتمد الباحثان الاستبانة بوصفها أداةً لجمع البيانات وذلك من خلال تطبيقها على عينة عشوائية مكونة من (408) معلمًا ومعلمة، للعام الدراسي2023/2024م. ولمعالجة بيانات البحث استخدم برنامج الرزم الإحصائية للعلوم الإنسانية (SPSS)، وكشفت نتائج الدراسة عن وجود علاقة إيجابية للرضا عن الحياة بأبعاده الثلاثة على الأداء الوظيفي، وفي ضوء تلك النتائج تضمن البحث جملة من التوصيات للقائمين على النظام التعليمي اليمني عمومًا، أهمها ضرورة تقديم الرعاية المناسبة والدعم الكامل للمعلمين في المدارس الحكومية في الجمهورية اليمنية بما يتناسب مع مكانتهم الاجتماعية ودورهم في تنمية المجتمع والارتقاء به، حيث إن المعلم يعتبر اللبنة الأساسية للنهوض بالأجيال من خلال دوره الهام والفعال، تقدير جهود المعلمين من خلال تحفيزهم مادياً ومعنوياً، مما يؤدي إلى تحسين أداؤهم الوظيفي. ABSTRACT Teachers play a key role in the educational process; therefore, it is important to give them the necessary attention to ensure they effectively fulfil their pedagogical responsibilities. Hence the current research aims to examine the influence of economic life satisfaction, health life satisfaction, social respect on job performance of secondary school teachers in Yemen. The researcher adopted a descriptive method, utilizing a survey that aligns with the nature and objectives of the study. Moreover, the researcher used a questionnaire as a data collection instrument and applied it on the random sample that consists of 408 male and female teachers in secondary schools for the academic year 2023/2024 in Yemen. The results showed a positive relationship between life satisfaction with its three dimensions on job performance. Based on the study's findings, the researcher provided several recommendations for educational officials in Yemen. The most significant of these recommendations is the need to ensure adequate support and attention for teachers in government schools, in alignment with their critical role in societal development. Teachers play an essential role in shaping future generations. Recognizing their efforts through financial and moral incentives can significantly enhance their job performance.